Nonlinearity of dose-response functions for carcinogenicity. - Hoel, D G (1994)
Carcinogenesis data for 315 chemicals were obtained from the National Cancer Institute-National Toxicology Program (NCI-NTP) bioassay programs and were analyzed to examine the shape of carcinogenesis dose-response curves. Tumor site data were more often consistent with a quadratic response than with a linear response, suggesting that the routine use of linear dose-response models will often overestimate risk. Information from in vivo short-term mutagenicity and genotoxicity assays was also obtained for most of these rodent bioassays. It was found that there were no clear relationships between the shape of the carcinogenesis dose-response curve and the result of the short-term test. These observations argue against the concept that carcinogens that are positive in a short-term assay be regulated using a linear dose-response curve and those that are negative be regulated using a sublinear dose-response curve or a safety factor approach.